Telomere length is greater in ALS than in controls: a whole genome sequencing study. Issue 3 (3rd April 2019) - Al Khleifat, Ahmad; Iacoangeli, Alfredo; Shatunov, Aleksey; Fang, Ton; Sproviero, William; Jones, Ashley R.; Opie-Martin, Sarah; Morrison, Karen E.; Shaw, Pamela J.; Shaw, Christopher E.; Powell, John F.; Dobson, Richard; et al.
Abstract: Background: Amyotrophic lateral sclerosis is a neurodegenerative disease of motor neurons resulting in progressive paralysis and death, typically within 3–5 years. Although the heritability of ALS is about 60%, only about 11% is explained by common gene variants, suggesting that other forms of genetic variation are important. Telomeres maintain DNA integrity during cellular replication and shorten naturally with age. Gender and age are risk factors for ALS and also associated with telomere length. We therefore investigated telomere length in ALS. Methods: We estimated telomere length by applying a bioinformatics analysis to whole genome sequence data of leukocyte-derived DNA from people with ALS and age and gender-matched matched controls in a UK population. We tested the association of telomere length with ALS and ALS survival. Results: There were 1241 people with ALS and 335 controls. The median age for ALS was 62.5 years and for controls, 60.1 years, with a male–female ratio of 62:38. Accounting for age and sex, there was a 9% increase of telomere length in ALS compared to matched controls. Those with longer telomeres had a 16% increase in median survival. Of nine SNPs associated with telomere length, two were also associated with ALS: rs8105767 near the ZNF208 gene ( p = 1.29 × 10 −4 ) and rs6772228 ( p = 0.001), which is in an intron for the PXK gene. Conclusions: Longer telomeres in leukocyte-derived DNA are associated with ALS, and with increased survival in those with ALS.